A NEW INTERPRETATION OF THE COMPOUND STROBILAR STRUCTURES OF CORDAITES AND CONIFERS - HSUAN KENG (REINWARDTIA, 1980)
The compound strobili of cordaites and conifers (e.g. Amentotaxiis) is interpreted by the application, of the telome theory. Homologies of organization among the strobilar structures and the pinnate phylloclade of Phyllocladus are also suggested.